Corporate Social Responsibility dalam Perspektif Islam (Mazahib, 2014)
Corporate Social Responsibility (CSR) should be applied within the organization or company. With the CSR, it will make the perpetrators of environmental organizations appreciate the place he was. To implement CSR companies must recognize that the problems of society is theirs too. Not only that, the company also must be willing to handle it. It was essentially to implement CSR. So just to acknowledge what problems exist in the community and it becomes part of them, the CSR is easier to do. Strategic plan of CSR programs can be will contribute to the reduction of poverty and social injustice in society. In the Islamic perspective, CSR is a realization of the concept of ihsan as the culmination of a very noble ethical. Ihsan is carrying out good deeds that can provide benefit to others in order to obtain the blessing of Allah.